A model for electromigration induced flow in liquid metals. (1st September 2017) - Kumar, Sumit; Kumar, Praveen; Pratap, Rudra
Abstract: Electromigration in liquid metals can be used for mass transport over a considerable length with micro- and nano-scale flow features. Exploitation of this phenomenon, however, requires a sound understanding of the liquid metal flow under an applied electric field. Depending on the sign of the effective charge number, Z *, liquid metals flow along a set direction under the applied electric field. A few liquid metals, e.g. Ga, Sn, etc, flow in the direction of the electric field, while a few others, e.g. Pb, flow in the opposite direction. Here, we propose a new model for predicting the direction of the aforementioned flow for a given liquid metal. Our model incorporates Lennard-Jones potential into the cell model of liquids in order to calculate the value of Z * as a function of temperature. We then carry out experiments on a few metals to validate the model and show that it indeed correctly predicts the ensuing flow.